Systematic review: Analysis of the use of D-limonene to reduce the environmental impact of discarded expanded polystyrene (EPS) - Mollehuara Huayas, Michelle Angely (2022)
The article presents a systematic review on the use of D-limonene with the aim of analyzing its efficiency to reduce the environmental impact of expanded polystyrene (EPS). Initially, an analysis of the life cycle of the EPS was carried out in a general way to identify the stage where the greatest impact on the environment is evident. Subsequently, primary sources were examined that raise the issue of reducing EPS using this green solvent, in view of the fact that it generates sustainability through recycling, optimization and application of various methods that could allow the circular economy of this waste in order to be applied in the industrial field and contribute to the socio-environmental aspect. Finally, the importance of this solvent was demonstrated according to the analysis and evaluation of each EPS recycling examining country.